Pitadas afro-indígenas: a Cozinha de Santo de Mãe Rita Preta como lugar de memória - Valente, Tadeu Rena (2019)
It aims to discuss some aspects of the relationship between the Saint's kitchen and the personal experiences of individuals participating in those cultural practices, showing how literature and life stories intertwine in discourses which mark a cultural identity. It is anchored by the need to deepen the research on the sociocultural formation of individuals and social groups’ food preferences besides focusing on the cuisine as an intangible cultural historical heritage to be preserved. The study focuses on the personal account of Mother Rita, who lives in the city of Santa Rita-PB, comprising the public and private spaces of this subject, a way of conceiving the Saint's kitchen and the culinary practice developed there. Our concern is to perceive these manifestations as the result of an inheritance and meanwhile considering the contexts of production in which these cultural practices exist, highlighting the voices of the individuals inserted in them. Our objectives are as follows. We prioritize the preservation of the Saint’s kitchen through the social memory, we relate its flavors in a kind of inextricable memory between space and experiences; we seek to understand Mother Rita and Mother Expedita’s thoughts on the knowledge and flavors in the Saint’s kitchen. Finally, we seek to identify the customs, rituals, clothing, food, religiousness and even mentality which mark the cultural and religious practice in Mother Rita’s house. Through the methodology of life history, using the technique of interview and participatory observation, it is possible to get to know Mother Rita and her habitat closely, identifying the mechanisms by which she creates her personal experience. The approximation of her private universe and the discussion of the concepts of memory, identity and morality allow us to perceive the relation between the practices that she exercises and the personal account of her history. The analysis makes it possible to understand the Saint’s kitchen as a universe belonging to Mother Rita from the activities and discourses inherent to religious practices and implicit sociocultural relations between her and members who worship such practices. It is said that food preferences are defined social and culturally, and that the formation of the palate, as conceptualized by Luís da Câmara Cascudo, is directly related to the cultural patterns of a particular social group, permeated by social memory, feelings of belonging and identification. Thus, if food and cooking are dealt with as an immaterial cultural heritage, their protection becomes indispensable.